2022
DOI: 10.1002/bab.2353
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the biosynthetic potential of Penicillium roqueforti for hyperproduction of the immunosuppressant mycophenolic acid: Gamma radiation mutagenesis and response surface optimization of fermentation medium

Abstract: Based on the broad clinical utility of the immunosuppressant mycophenolic acid (MPA), this article aims to intensify the biosynthetic potential of Penicillium roqueforti for more effective hyperproduction of the drug. Several mutants were generated from irradiation mutagenesis and screened. Two strains (GM1013 and GM1093) presented an elevated MPA productivity with significant yield constancy over 10 subsequent generations. By investigating the effect of some phosphorous sources and mineral salts on MPA produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
(84 reference statements)
1
6
0
Order By: Relevance
“…Also, the same irradiation dose improved production of the cardiac glycoside digoxin to a five-fold increase by Epicoccum nigrum (El-Sayed et al 2020b ). Moreover, the same effect of exposure to gamma rays on the survival and the fungal growth was observed by previous reports (Awan et al 2011 ; El-Sayed and Zaki 2022 ; El-Sayed et al 2019a ; b ; c ). Previous reports concluded the effect of gamma rays as an energetic ionizing radiation in induction of mutations in the exposed cells (Thacker 1999 ) through the repair mechanism in genes of the DNA of the irradiated cells (Ismaiel et al 2014 , 2015 ; Zaki et al 2020 ; Zaki and El-Sayed 2021 ).…”
Section: Discussionsupporting
confidence: 83%
“…Also, the same irradiation dose improved production of the cardiac glycoside digoxin to a five-fold increase by Epicoccum nigrum (El-Sayed et al 2020b ). Moreover, the same effect of exposure to gamma rays on the survival and the fungal growth was observed by previous reports (Awan et al 2011 ; El-Sayed and Zaki 2022 ; El-Sayed et al 2019a ; b ; c ). Previous reports concluded the effect of gamma rays as an energetic ionizing radiation in induction of mutations in the exposed cells (Thacker 1999 ) through the repair mechanism in genes of the DNA of the irradiated cells (Ismaiel et al 2014 , 2015 ; Zaki et al 2020 ; Zaki and El-Sayed 2021 ).…”
Section: Discussionsupporting
confidence: 83%
“…In generally, the observed increase in the prepared ZnONPs yield could be mainly attributed to the gamma ray’s exposure of the fungal cells prior to the preparation of the cell-free filtrate used in the preparation of NPs. Exposure of the fungus cells to gamma rays might induced mutations (El-Sayed et al 2022a ; Hazaa et al 2022 ) in these cells resulting in the over-production of all the active metabolites and enzymes responsible (El-Sayed et al 2022c ; El-Sayed and Zaki 2022 ) for the bio-reduction of zinc sulfate salt and intensifying the formation of high concentrations of ZnONPs. Previous reports showed that the irradiation by gamma rays at some specific doses was successfully used for enhancing the production of various fungal metabolites (El-Sayed 2021 ; Zaki and El-Sayed 2021 ; El-Sayed et al 2019a , b , c ; El-Sayed et al 2020c , d , e , f ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, fungi-mediated synthesis of several nanomaterials have magnificently emerged as the most advantageous (Grasso et al 2021 ). Over the years, fungi have been employed extensively in several industrial applications (Dorcheh and Vahabi 2016 ; El-Sayed and Zaki 2022 ) as the most efficient biotechnological factories due to their flexibility, simplicity, easy maintenance, and tolerance. In this regard, the use of endophytes has emerged as a new research area for green and cost-effective production of several NPs.…”
Section: Introductionmentioning
confidence: 99%